2017
DOI: 10.1038/s41443-017-0013-3
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of variation in technique and variation in accuracy of measurement in penile length measurement

Abstract: Accurate data regarding the size of the erect penis is of great importance to several disciplines working with male patients, but little data exists on the best technique to measure penile length. While some previous small studies have suggested good correlation between stretched penile length, others have shown significant variability. Penile girth has been less well studied, and little data exist on the possible errors induced by differing observers and different techniques. Much of the published data report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Erect penile length and curvature was measured pre-and postoperatively during artificial erection. Length's measurement was done from the pubic bone to the tip of the glans [13]. As adequate length measurement in case of severe curvature is difficult, the concave side of curvature was measured in these cases (from point of maximum curvature to pubic bone and to tip of glans).…”
Section: Methodsmentioning
confidence: 99%
“…Erect penile length and curvature was measured pre-and postoperatively during artificial erection. Length's measurement was done from the pubic bone to the tip of the glans [13]. As adequate length measurement in case of severe curvature is difficult, the concave side of curvature was measured in these cases (from point of maximum curvature to pubic bone and to tip of glans).…”
Section: Methodsmentioning
confidence: 99%
“…Among them, Habous et al . reported that PFL is the only accurate parameter to predict erect size . We also note that penile size is influenced by anthropometric measurements, such as height, weight and, especially, body mass index.…”
mentioning
confidence: 61%
“…Physical examination and penile ultra-sonography determined location, number, and size of plaques of the tunica albuginea of the penis. Penile length was measured from suprapubic skin to distal glans in the stretched flaccid penis, as described previously [18]. Color duplex Doppler ultra-sonography (CDDU) of the penis combined with intracavernous injection of 20 µg Prostavasin was performed preoperatively according to established standard operating procedures [19].…”
Section: Methodsmentioning
confidence: 99%